Ethnic gatekeeping on the shopfloor: a study of bases, motives and approaches. (February 2016) - Harris, Lloyd C; Ogbonna, Emmanuel
Recent contributions on the discrimination of black and minority ethnic (BME) groups in organizations have suggested that overt forms of discrimination are now 'old-fashioned' and researchers are urged to focus on identifying different, 'modern' forms of discrimination. These are, however, set against studies that continue to report evidence of overt racism in organizations. This article argues that it may be premature and potentially counterproductive to celebrate the demise of overt discrimination in that such binary classification ('old-fashioned' and 'modern') may discourage efforts to investigate the full gamut of experiences of BME groups. The article contends that additional insights will be gained by concurrently studying not only the victims and the perpetrators of discrimination but also the organizational context in which discrimination occurs. Through the theoretical lens of gatekeeping, the article presents evidence of shopfloor discrimination against BME groups that is neither fully overt nor entirely covert.